Current and further outlook on the protective potential of Antrodia camphorata against neurological disorders - Li, Weiling; Wan, Pin; Qiao, Jialu; Liu, Yuchen; Peng, Qian; Zhang, Zehua; Shu, Xiji; Xia, Yiyuan; Sun, Binlian (Frontiers in Pharmacology, 2024)
Prevalent neurological disorders such as Alzheimer’s disease, Parkinson’s disease, and stroke are increasingly becoming a global burden as society ages. It is well-known that degeneration and loss of neurons are the fundamental underlying processes, but there are still no effective therapies for these neurological diseases. In recent years, plenty of studies have focused on the pharmacology and feasibility of natural products as new strategies for the development of drugs that target neurological disorders. Antrodia camphorata has become one of the most promising candidates, and the crude extracts and some active metabolites of it have been reported to play various pharmacological activities to alleviate neurological symptoms at cellular and molecular levels. This review highlights the current evidence of Antrodia camphorata against neurological disorders, including safety evaluation, metabolism, blood-brain barrier penetration, neuroprotective activities, and the potential on regulating the gut-microbiome-brain axis. Furthermore, potential strategies to resolve problematic issues identified in previous studies are also discussed. We aim to provide an overview for the ongoing development and utilization of Antrodia camphorata in cerebral neuropathology.